2 - (Re-)Telling the War Story, Healing the Wounds: A Bibliotherapeutic Reading of Ahmadou Kourouma’s Allah is Not Obliged: Sola Owonibi, Oluyinka Ojedokun & Omon Osiki - Owonibi, Sola; Ojedokun, Oluyinka; Osiki, Omon (Africa Development, 2021)
The devastation associated with both civil conflicts and wars takes physical and emotional efforts to heal. There are works of African literature that have analysed war trauma, testimony an healing of emotional wounds utilising psychoanalytic perspectives. This article attempt to deepen analysis of such works using a bibliotherapeutic reading of Ahmadou Kourouma’s Allah is Not Obliged. This article adopts a psychoanalytic perspective of testimony and memory to analyse reading the war story, its traumatic impact and healing potential. This article fills a gap in the intellectual understanding of the role of literature (i.e., bibliotherapeutic) in healing the wounded souls. We employed a qualitative methodological approach by which a literary analysis of the novel is done. The literary text is complemented with an analysis of secondary materials related to civil war in Africa. Allah is Not Obliged testifies about war trauma and healing process among child soldiers through sharing of personal stories and experiences connected to war. The various warring countries captured in the text are a metaphor for his patients – sick bodies in need of medical attention. Sicknesses are strong metaphors for social deviations. Additionally, the novel stressed the importance of writing, telling, and language as methods of traumatic flashback and bringing healing to child soldiers. We contend that reading Allah is Not Obliged can provide the reader with help in dealing with trauma of war.